Diagnostic leaves for evaluating dwarf cashew nutritional status - Martins, Thais da Silva (2025)
Cashew tree (Anacardium occidentale L.) is a fruit species widely cultivated in Brazil, but the interest in evaluating this plant nutritional status is very recent, to the point there is still no defined diagnostic leaf. This study aimed to define the leaves that reflect the nutritional status of dwarf cashews. Leaf samples were collected from a productive orchard established with four dwarf cashew clones: ‘CCP 76’, ‘BRS 189’, ‘BRS 226’, and ‘BRS 265’. Leaf sampling was performed over four consecutive years, at the beginning of the flowering season and the emergence of inflorescences with floral buds. Sampling was carried out from the first to the sixth fully expanded (mature) leaf, from the inflorescence towards the base of the branch. Total leaf content of macronutrients, micronutrients, and Na were quantified. Multi-element index variables were obtained using Compositional Nutrient Diagnosis (CND) methodology, and total leaf concentrations were correlated with cashew nut yields. The pair of leaves closest to the base of the branch, 5th and 6th leaves, showed a balanced index of nutrients, including N, K, Ca, S, Mn, and Zn. These leaves were also positively correlated with cashew nut yield and exhibited lower coefficients of variation for most of the analyzed nutrients. Thereby, the 5th and 6th leaves are recommended as diagnostic leaves for evaluating the nutritional status of dwarf cashews.